NETWORKS AND TIES. THE ECONOMICAL POWER HOLDERS OF ALBURNUS MAIOR - Rada Maria Varga (Journal of Ancient History and Archaeology)
Alburnus Maior is one of the best-documented and most interesting Roman provincial rural societies. It provided historians with a most complex source: the wax tablets, representing contracts and other juridical documents, hid in a mine gallery when tragedy struck (the Marcomannic attack of 168 AD) and never recovered by their owners. In the current article, based on micro-historical information offered by these unique sources, we will present an analysis local society, with a focus on its socio-economical networks, the people which formed them and the ties existing between them.